The importance of identity in a teacher professional learning community - Chauraya, Million (Human Sciences Research Council, 2019)
The literature on professional learning communities (PLCs) highlights the significance of such communities for sustained teacher professional learning that is likely to result in the improvement of teaching practices (Borko 2004; Brusling 2005). Research studies have tended to focus on two aspects of PLCs: (1) how learning occurs and (2) the success and sustainability of PLCs. The focus of this chapter is on the latter.